Lipoprotein-Associated Phospholipase A2 Is a Risk Factor for Patients With Parkinson’s Disease - Wu, Zubo; Wu, Suyuan; Liang, Tao; Wang, Lin (Frontiers in Neuroscience, 2021)
Abstract Objective: To explore the association between lipoprotein-related phospholipase A2 (Lp-PLA2) and the risk of Parkinson's disease (PD). Methods: A case-control study involving 58 hospitalized PD patients and 60 healthy controls was carried out. Serum Lp-PLA2 level was detected. According to the disease course and severity, PD patients were subdivided to analyze the clinical value of Lp-PLA2. Relationship between Lp-PLA2 and PD risk was analyzed by logistic regression. Diagnostic value of Lp-PLA2 in PD patients was investigated using receiver’s operator characteristic curves. Results: Lp-PLA2 level was significantly higher in the PD patients compared with the controls, and was significantly and positively correlated with the Hoehn-Yahr stage. The serum Lp-PLA2 level and Hoehn-Yahr stage of PD patients with a longer disease course were significantly higher than those with a shorter disease course. PD patients with milder conditions had significantly lower serum Lp-PLA2 levels than patients with severer conditions. Multivariable logistic regression analysis indicated higher Lp-PLA2 level was an independent risk factor of PD patients. Moreover, the area under the curve for Lp-PLA2 was 0.703, which was between those of homocysteine and serum amylase A. Conclusion: To our knowledge, this is the first study to show that increased level of Lp-PLA2 is associated with the risk of PD. Lp-PLA2 may be used for early detection of PD, and provides an effective intervention target for clinical treatment of PD.